A method for controlling the reaction interface oxide layer of a thick-gauge GPa-grade hot-dip galvanized dual-phase steel
Patent Information
- Application Number
- CN202611162925.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-08-03
AI Technical Summary
[0007]为克服现有技术的不足,本发明的目的是提供一种厚规格GPa级热镀锌双相钢反应界面氧化层控制方法,解决厚规格GPa级热镀锌双相钢反应界面氧化层难以精准调控、易导致镀层剥落及漏镀的质量缺陷问题
本发明通过热轧梯度降温控制,镀锌梯度退火工艺与精准还原气氛的协同作用,在带钢表面形成均匀致密的预还原层,从源头抑制氧化层的无序生长;通过优化锌液成分与浸镀参数,实现界面反应的调控,显著提升镀层与基体的结合力,经检测,镀层结合力符合胶粘要求,满足高强度、厚规格双相钢的严苛使用要求。本发明可极大程度抑制Mn元素向反应界面富集,获得薄而致密的含铝抑制层,有效解决现有技术中氧化层控制精度不足、镀层结合力差的难题,且工艺参数稳定可控,适用于工业化大规模生产。
Smart Images

Figure CN122669176B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of steel plate production technology, and particularly relates to a method for controlling the oxide layer at the reaction interface of thick-gauge GPa-grade hot-dip galvanized duplex steel. Background Technology
[0002] High-strength hot-dip galvanized duplex steel has become a core choice for automotive body materials due to its excellent strength-toughness ratio, low yield strength ratio, and good corrosion resistance. In particular, GPa-grade hot-dip galvanized duplex steel, with its high strength and excellent corrosion resistance, excels in meeting lightweight and structural strength requirements, making it a core material for critical components such as body structural parts and chassis load-bearing parts. However, during the hot-dip galvanizing process, this material is susceptible to damage from multiple factors, including the annealing furnace atmosphere, selective oxidation of alloying elements, and interfacial reaction kinetics. This can easily lead to the formation of a non-uniform silicon and manganese oxide layer at the interface between the steel substrate and the galvanized layer, resulting in defects such as insufficient coating adhesion and incomplete coating, severely restricting product surface quality and service performance.
[0003] In the production process of thick-gauge GPa-grade hot-dip galvanized duplex steel, alloying elements such as Cr, Mn, and Si are added to ensure the steel's strength. However, in the high-temperature environment of the annealing furnace on the galvanizing line, these alloying elements readily react with trace amounts of water vapor or oxygen in the protective reducing gas, forming oxide particles or even continuous oxide films on the steel plate surface. Because these oxides are non-wetting to the molten zinc, they directly hinder the contact between the molten zinc and the steel substrate, ultimately leading to numerous uncoated defects on the surface of the galvanized duplex steel, severely affecting the product's surface quality and service performance.
[0004] In existing technologies, although some processes attempt to reduce surface oxidation by adjusting parameters such as dew point, atmosphere, and oxygen content in the furnace to achieve internal oxidation of alloying elements, for thick products, the uneven heat conduction and extended diffusion paths of alloying elements caused by the thickness significantly increase the difficulty of oxide layer control. Existing parameter control methods are difficult to accurately adapt to the interface reaction characteristics of thick products, and cannot effectively balance the relationship between alloying element oxidation and zinc plating interface bonding performance. Therefore, it is still difficult to completely solve core problems such as surface plating defects and insufficient zinc layer adhesion.
[0005] In addition, in order to suppress the ferrite and bainite phase transformation during the galvanizing process of thick-gauge GPa-grade hot-dip galvanized duplex steel at 460℃ and improve the hardenability of the steel, it is necessary to further increase the amount of Mn added. This, to some extent, exacerbates the risk of selective oxidation of Mn, resulting in a more complex composition and structure of the oxide layer at the reaction interface, which further increases the difficulty of precise control of the oxide layer.
[0006] Therefore, existing technologies are insufficient to meet the requirements of precise control of the oxide layer at the reaction interface for thick-gauge GPa-grade hot-dip galvanized duplex steel. There is an urgent need to develop a targeted and highly adaptable oxide layer control method to effectively inhibit the formation of harmful surface oxide layers, ensure the bonding quality of the galvanized interface, improve the product performance and production stability of thick-gauge GPa-grade hot-dip galvanized duplex steel, and meet the stringent requirements of the automotive industry for high-strength and high-quality steel. Summary of the Invention
[0007] To overcome the shortcomings of existing technologies, the purpose of this invention is to provide a method for controlling the oxide layer at the reaction interface of thick-gauge GPa-grade hot-dip galvanized duplex steel. This method addresses the quality defects of difficult-to-precisely controllable oxide layer at the reaction interface of thick-gauge GPa-grade hot-dip galvanized duplex steel, which easily leads to coating peeling and incomplete coating. By systematically integrating the entire process of hot rolling gradient cooling, pickling, pre-oxidation, annealing reduction, and galvanizing interface reaction, an oxide layer control system adapted to the characteristics of thick-gauge duplex steel is constructed. This system enables the control of the thickness, composition, and structure of the interface oxide layer, thereby improving coating adhesion, corrosion resistance, and forming stability.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for controlling the oxide layer at the reactive interface of thick-gauge GPa-grade hot-dip galvanized duplex steel includes the following steps: 1) Hot rolling: A multi-stage hot rolling cooling process is adopted; 2) Pickling: belt speed is 85-95 m / min, acid temperature is 85-88℃; 3) Pretreatment: The strip steel is surface cleaned and dried at a temperature of 130-150℃ for 4-5 minutes. 4) Annealing and Reduction: The strip steel is fed into a continuous annealing furnace at a speed of 50–52 m / min. A gradient heating process is adopted, first heating to 820–845℃ at 18–22℃ / s, then heating to 850–865℃ at 5–8℃ / s, and holding for 2–3 seconds; subsequently cooling to 680–690℃ at 8–10℃ / s, and holding for 3–5 seconds; 15%–18% H2 and 81%–85% N2 by volume are introduced into the furnace, and the reduction dew point is controlled at -45℃ to -50℃; then it enters the pre-oxidation stage, using a nitrogen-oxygen mixed gas with a flow rate of 12–15 m³ / s. 3 / h, the humidification dew point is set to -8℃~-10℃, and the grate dew point is set to -15℃~-20℃; 5) Hot-dip galvanizing: The annealed strip steel is immersed in molten zinc at a temperature of 455-465℃ for 4-6 seconds. 6) Post-treatment: Use an air knife to purge the strip at a pressure of 0.11–0.15 MPa and a distance of 15–25 mm between the air knife and the strip to remove excess zinc liquid from the strip surface. Then, air cool to 200–300°C at a cooling rate of 15–30°C / s, and then water cool to room temperature at a cooling rate of 30–50°C / s.
[0009] The hot rolling process involves heating at a temperature of 1200–1250°C, followed by rough rolling and then finish rolling. The initial rough rolling temperature is 1080–1130°C, and the final finish rolling temperature is 820–850°C. The coiling is carried out in two stages of water cooling. The first stage involves water cooling to 600–630°C, followed by air cooling to 540–560°C, and the second stage involves water cooling to 180–220°C before coiling.
[0010] The chemical composition of the zinc liquid, by weight percentage, includes: Zn ≥ 99.5%, Al 0.22%~0.26%, Pb ≤ 0.002%, with the balance being unavoidable impurities.
[0011] The zinc solution also contains 30-50 ppm of rare earth element Ce.
[0012] The thickness of the thick-gauge GPa grade hot-dip galvanized duplex steel plate is 2.5 to 3.5 mm.
[0013] The chemical composition of the aforementioned thick-gauge GPa grade hot-dip galvanized duplex steel, by weight percentage, includes: C: 0.07%~0.12%, Mn: 2.0%~2.3%, Si: 0.4%~0.6%, P≤0.025%, Cr: 0.30%~0.5%, Nb: 0.015%~0.035%, Mo: 0.10%~0.20%, Als: 0.020%~0.05%, balance Fe.
[0014] The microstructure of the thick-gauge GPa grade hot-dip galvanized duplex steel is a ferrite-martensite dual-phase structure, with a martensite volume fraction of 30% to 45%.
[0015] The nitrogen-oxygen mixture contains, by volume percentage: 20%–25% oxygen, with the remainder being nitrogen and unavoidable impurity gases.
[0016] In step 6), the cooling is a combination of air cooling and water cooling. First, air cooling is performed to 200-300°C, and then water cooling is performed to room temperature.
[0017] Compared with the prior art, the beneficial effects of the present invention are: This invention utilizes the synergistic effect of hot rolling gradient cooling, galvanizing gradient annealing, and precise reducing atmosphere to form a uniform and dense pre-reduced layer on the strip steel surface, suppressing the disordered growth of the oxide layer from the source. By optimizing the zinc bath composition and immersion parameters, the interfacial reaction is controlled, significantly improving the adhesion between the coating and the substrate. Testing shows that the coating adhesion meets adhesive requirements, satisfying the stringent requirements for high-strength, thick-gauge duplex steel. This invention can greatly suppress the enrichment of Mn elements at the reaction interface, obtaining a thin and dense aluminum-containing inhibition layer, effectively solving the problems of insufficient oxide layer control precision and poor coating adhesion in existing technologies. Furthermore, the process parameters are stable and controllable, making it suitable for large-scale industrial production. Attached Figure Description
[0018] Figure 1 This is a backscattered electron image (BSO) of a 2.5mm thick GPa grade strip produced using conventional methods.
[0019] Figure 2 This is an elemental line scan of 2.5mm thick GPa grade strip steel produced using conventional methods. Figure One (Si element).
[0020] Figure 3 This is an elemental line scan of 2.5mm thick GPa grade strip steel produced using conventional methods. Figure Two (Mn element).
[0021] Figure 4 This is an elemental line scan of 2.5mm thick GPa grade strip steel produced using conventional methods. Figure Three (All elements).
[0022] Figure 5 This is a cross-sectional microstructure diagram (secondary electron image) of a 2.5mm thick GPa grade strip produced by conventional methods.
[0023] Figure 6 This is an elemental surface scan of a 2.5mm thick GPa grade strip produced using conventional methods. Figure One (Element O).
[0024] Figure 7 This is an elemental surface scan of a 2.5mm thick GPa grade strip produced using conventional methods. Figure Two (Mn element).
[0025] Figure 8 This is an elemental surface scan of a 2.5mm thick GPa grade strip produced using conventional methods. Figure Three (Al element).
[0026] Figure 9 This is a surface morphology diagram of a 2.5mm thick GPa grade steel strip inhibition layer produced by conventional methods.
[0027] Figure 10 This is a cross-sectional microstructure (backscattered electron image) of a 2.5mm thick GPa grade strip produced by the method of this invention.
[0028] Figure 11 This is an elemental line scan of 2.5mm thick GPa grade strip steel produced by the method of this invention. Figure One (Mn element).
[0029] Figure 12 This is an elemental line scan of 2.5mm thick GPa grade strip steel produced by the method of this invention. Figure Two (Si element).
[0030] Figure 13 This is a cross-sectional microstructure (secondary electron image) of a 2.5mm thick GPa grade strip produced by the method of this invention.
[0031] Figure 14 This is an elemental surface scan of a 2.5mm thick GPa grade strip produced by the method of this invention. Figure One (Element O).
[0032] Figure 15 This is an elemental surface scan of a 2.5mm thick GPa grade strip produced by the method of this invention. Figure Two (Al element).
[0033] Figure 16 This is an elemental surface scan of a 2.5mm thick GPa grade strip produced by the method of this invention. Figure Three (Mn element).
[0034] Figure 17 This is a surface morphology diagram of the 2.5mm thick GPa grade steel strip suppression layer produced by the method of the present invention.
[0035] Figure 18 This is a hot rolling process curve diagram of the present invention.
[0036] Figure 19 This is a hot rolling process curve diagram of Example 1. Detailed Implementation
[0037] The present invention will now be described in detail with reference to the accompanying drawings, but it should be noted that the implementation of the present invention is not limited to the following embodiments.
[0038] A method for controlling the oxide layer at the reaction interface of thick-gauge GPa-grade hot-dip galvanized duplex steel is developed. By precisely controlling the annealing process, reducing atmosphere, and zinc bath composition, the thickness, composition, and structure of the oxide layer at the reaction interface are controlled, thereby improving coating adhesion and product quality.
[0039] The thickness of the GPa grade hot-dip galvanized duplex steel sheet is 2.5–3.5 mm. The microstructure of this hot-dip galvanized duplex steel is a ferrite-martensite dual-phase structure, with a martensite volume fraction of 30%–45%. The method for controlling the oxide layer at the reaction interface of hot-dip galvanized duplex steel includes the following steps: 1) Hot Rolling: To minimize the surface enrichment of Si and Mn oxides in subsequent rolling processes, a multi-stage hot rolling cooling process is employed. This involves controlling the temperature range to ensure the desired microstructure characteristics, and rapid cooling to facilitate structural separation of the oxide layer from the substrate, providing favorable conditions for subsequent pickling. Specifically: the heating temperature is 1200–1250℃, with rough rolling followed by finish rolling. The initial rough rolling temperature is 1080–1130℃, and the final finish rolling temperature is 820–850℃. The coiling is then carried out in two stages: the first stage involves water cooling to 600–630℃, followed by air cooling to 540–560℃, and the second stage involves water cooling to 180–220℃ before coiling.
[0040] 2) Pickling: To improve the removal of iron oxide scale, pickling is carried out with a belt speed of 85-95 m / min and an acid temperature of 85-88℃. This process is highly related to the strip steel composition, hot rolling process, and the thickness and composition of the iron oxide scale in the preceding process. Therefore, it is necessary to set the belt speed and acid temperature separately for this composition and hot rolling process. Too high or too low belt speed and acid temperature will result in over-pickling or under-pickling of the strip steel, which will affect the surface quality of subsequent galvanizing.
[0041] 3) Pretreatment: Clean the surface of the strip steel to remove surface oil and impurities, and then dry it. The drying temperature is controlled at 130-150℃ for 4-5 minutes to ensure that the surface of the strip steel is dry and clean, laying the foundation for subsequent processes.
[0042] 4) Annealing and reduction: The strip steel is fed into a continuous annealing furnace at a speed of 50-52 m / min. A gradient heating process is adopted, first heating to 820-845℃ at 18-22℃ / s, then heating to 850-865℃ at 5-8℃ / s, and holding for 2-3s to fully austenitize the duplex steel matrix; then cooling to 680-690℃ at 8-10℃ / s and holding for 3-5s, while ensuring the rapid cooling temperature gradient, promoting the dynamic rebalancing of carbon elements, and ensuring the alternating distribution of ferrite and martensite duplex structures. The furnace is purged with 15%–18% H2 and 81%–85% N2 by volume, with the reduction dew point controlled at -45℃ to -50℃. Precise atmosphere and temperature control reduces the holding time in the high-temperature range, controlling the temperature gradient along the strip's thickness. This ensures the surface temperature remains consistently higher than the core, causing surface volume expansion and compressive stress from the surface inwards. This compresses the diffusion channels of Si and Mn elements along the grain boundaries, suppressing the tendency for element enrichment on the surface during heating. A pre-oxidation process is added, using a nitrogen-oxygen mixed gas (20–25% oxygen, the remainder being nitrogen and unavoidable impurity gases) with a flow rate of 12–15 m³ / h. 3 / h, the humidification dew point is set to -8℃~-10℃. This process is mainly formulated based on the specific strip steel composition and previous processes in this invention. Since the manganese and silicon content of the strip steel in this hot-dip galvanized duplex steel is high, the structure and thickness of the pre-oxidation layer directly affect the setting of the subsequent reduction section and the belt speed. The dew point of the grate is set to -15℃~-20℃ to ensure the control of zinc ash on the strip steel surface and the adhesion of the coating.
[0043] 5) Hot-dip galvanizing: Annealed steel strip is immersed in molten zinc at a temperature of 455–465℃ for 4–6 seconds. The chemical composition of the zinc bath, by weight percentage, includes: Zn ≥ 99.5%, Al 0.22%–0.26%, Pb ≤ 0.002%, with the balance being unavoidable impurities. Precise addition of aluminum allows for preferential reaction with residual trace oxygen on the steel strip surface, forming a thin and uniform interfacial reaction layer. Simultaneously, it inhibits excessive reaction between the zinc bath and the substrate, preventing oxide layer thickening. Strict control of the immersion time reduces the reaction time between the steel strip and the zinc bath, further controlling the oxide layer growth rate. 30–50 ppm of rare earth element Ce can also be added to the zinc bath. Rare earth elements can refine the interfacial reaction layer grains, improve the density and stability of the oxide layer, and further enhance the adhesion between the coating and the substrate.
[0044] 6) Post-treatment: Air knife purging is used at a pressure of 0.11–0.15 MPa, with a distance of 15–25 mm between the air knife and the strip. Precise air knife parameters remove excess molten zinc from the strip surface. The strip is then air-cooled to 200–300°C at a rate of 15–30°C / s, followed by water cooling to room temperature at a rate of 30–50°C / s, completing the preparation of thick-gauge GPa-grade hot-dip galvanized duplex steel. Uniform cooling is ensured to achieve the required microstructure characteristics, preventing stress cracks in the interface oxide layer due to uneven cooling.
[0045] Example 1:
[0046] The chemical composition of thick-gauge GPa grade hot-dip galvanized duplex steel, by weight percentage, includes: C: 0.09%, Mn: 2.15%, Si: 0.52%, P: 0.020%, Cr: 0.40%, Nb: 0.025%, Mo: 0.16%, Als: 0.030%, balance Fe.
[0047] The duplex steel has a thickness of 2.5 mm and its matrix structure is a ferrite-martensite dual-phase structure with a martensite volume fraction of 43%. The method for controlling the oxide layer at the reaction interface of thick-gauge GPa-grade hot-dip galvanized duplex steel includes the following main steps: Hot rolling: A multi-stage hot rolling cooling process is adopted, with a heating temperature of 1200℃. Rough rolling is performed first, followed by finish rolling. The initial rolling temperature of rough rolling is 1100℃, and the final rolling temperature of finish rolling is 830℃. The coiling is carried out through two stages of water cooling. The first stage water cooling is reduced to 600℃, followed by air cooling to 550℃, and the second stage water cooling is reduced to 200℃ before coiling.
[0048] Pickling: belt speed 86m / min, acid temperature 87℃; Pretreatment: The thick GPa grade duplex steel strip is cleaned to remove surface oil and impurities, and then dried at 130℃ for 4 minutes to ensure that the strip surface is dry and clean.
[0049] Annealing and Reduction: The dried strip steel is fed into a continuous annealing furnace at a speed of 51 m / min. A gradient heating process is used, heating the strip steel to 822℃ at a heating rate of 18℃ / s, then heating it to 860℃ at a heating rate of 6℃ / s and holding it for 2 seconds to fully austenitize the duplex steel matrix. Subsequently, it is cooled to 686℃ at a cooling rate of 9℃ / s and held for 3 seconds to promote the uniform formation of the ferrite and martensite duplex structure. The annealing furnace is purged with 17% hydrogen and 83% nitrogen by volume, and the reduction dew point is controlled at -53℃. Pre-oxidation process: A nitrogen-oxygen mixed gas is purged at a flow rate of 12 m³ / min. 3 / h, the humidification dew point is set to -8℃, and the grate dew point is set to -16℃ to ensure the control of zinc ash on the strip surface and the adhesion of the coating.
[0050] Hot-dip galvanizing: The annealed strip steel is immersed in molten zinc at a temperature of 462℃ for 6 seconds. The zinc bath composition, by weight percentage, is: 99.5% zinc, 0.24% aluminum, 0.002% lead, with the remainder being unavoidable impurities. 45 ppm of rare earth element Ce may also be added to the zinc bath. This refines the grain structure of the interfacial reaction layer, improves the density and stability of the oxide layer, and further enhances the adhesion between the coating and the substrate.
[0051] Post-processing: After the strip steel exits the zinc bath, it is purged with an air knife at a pressure controlled at 0.15 MPa and a distance of 22 mm between the air knife and the strip steel to remove excess molten zinc from the surface. It is then first air-cooled to 240°C at a rate of 22°C / s, and then water-cooled to room temperature at a rate of 32°C / s to complete the preparation of thick-gauge GPa grade hot-dip galvanized duplex steel.
[0052] Example 2:
[0053] A method for controlling the oxide layer at the reactive interface of thick-gauge GPa-grade hot-dip galvanized duplex steel includes the following steps: Hot rolling process: A multi-stage hot rolling cooling process is adopted, with a heating temperature of 1230℃. Rough rolling is performed first, followed by finish rolling. The initial rolling temperature of rough rolling is 1095℃, and the final rolling temperature of finish rolling is 835℃. The coiling is carried out in two stages of water cooling. The first stage of water cooling is reduced to 615℃, followed by air cooling to 540℃, and the second stage of water cooling is reduced to 200℃ before coiling.
[0054] Pickling process: belt speed 90m / min, acid temperature 86℃.
[0055] Pre-treatment process: The strip steel is surface cleaned to remove surface oil and impurities, and then dried at a temperature of 140℃ for 4.5 minutes.
[0056] Annealing and reduction process: The dried strip steel is fed into a continuous annealing furnace at a speed of 51 m / min. A gradient heating process is used, heating the strip steel to 830℃ at a heating rate of 20℃ / s, then heating it to 855℃ at a heating rate of 7℃ / s and holding it at that temperature for 2.5s; subsequently, cooling it to 685℃ at a cooling rate of 9℃ / s and holding it at that temperature for 4s. 16% (by volume) hydrogen gas is introduced into the annealing furnace for reduction, with the dew point controlled at -48℃, and nitrogen comprising 84% of the gas volume. The pre-oxidation gas flow rate is 13 m³ / min. 3 / h, humidifier dew point set to -9℃, grate dew point set to -18℃.
[0057] Hot-dip galvanizing reaction process: The zinc bath temperature is controlled at 460℃, and the immersion time is controlled at 5s. The zinc bath composition by weight percentage is: zinc 99.5%, aluminum 0.23%, lead ≤0.002%, and the remainder being unavoidable impurities; 40ppm of rare earth element Ce is added to the zinc bath.
[0058] Post-processing steps: The air knife pressure is controlled at 0.13 MPa, and the distance between the air knife and the strip is 20 mm to remove excess zinc liquid from the surface of the strip. Then, it is first air-cooled to 260°C at a cooling rate of 23°C / s, and then water-cooled to room temperature at a cooling rate of 38°C / s to complete the preparation of thick-gauge GPa grade hot-dip galvanized duplex steel.
[0059] The thickness of this GPa grade duplex steel is 3.0 mm, and its chemical composition by weight percentage is: C 0.08%, Mn 2.20%, Si 0.48%, P 0.018%, Cr 0.35%, Nb 0.020%, Mo 0.18%, Als 0.025%, with the balance being Fe and unavoidable impurities; the volume fraction of martensite in the matrix is 38%.
[0060] Example 3:
[0061] A method for controlling the oxide layer at the reactive interface of thick-gauge GPa-grade hot-dip galvanized duplex steel includes the following steps: Hot rolling process: A multi-stage hot rolling cooling process is adopted, with a heating temperature of 1250℃. Rough rolling is performed first, followed by finish rolling. The initial rolling temperature of rough rolling is 1110℃, and the final rolling temperature of finish rolling is 845℃. The coiling is carried out in two stages of water cooling. The first stage of water cooling is reduced to 625℃, followed by air cooling to 555℃, and the second stage of water cooling is reduced to 210℃ before coiling.
[0062] Pickling process: belt speed 93m / min, acid temperature 88℃.
[0063] Pre-treatment process: The strip steel is cleaned to remove surface oil and impurities, and then dried at 145℃ for 5 minutes.
[0064] Annealing and reduction process: The dried strip steel is fed into a continuous annealing furnace at a speed of 52 m / min. A gradient heating process is used, heating the strip steel to 840℃ at a heating rate of 22℃ / s, then heating it to 862℃ at a heating rate of 8℃ / s and holding it at that temperature for 3 seconds; subsequently, it is cooled to 690℃ at a cooling rate of 10℃ / s and held at that temperature for 5 seconds. 18% (by volume) hydrogen gas is introduced into the annealing furnace for reduction, with the dew point controlled at -46℃, and nitrogen gas accounting for 82% of the volume. The pre-oxidation gas flow rate is 14 m³ / min. 3 / h, humidifier dew point set to -10℃, grate dew point set to -19℃.
[0065] Hot-dip galvanizing reaction process: The zinc bath temperature is controlled at 464℃, and the immersion time is controlled at 6s. The zinc bath composition by weight percentage is: zinc 99.5%, aluminum 0.25%, lead ≤0.002%, and the remainder is unavoidable impurities; 48ppm of rare earth element Ce is added to the zinc bath.
[0066] Post-processing steps: The air knife pressure is controlled at 0.14 MPa, and the distance between the air knife and the strip is 24 mm to remove excess zinc liquid from the surface of the strip. Then, it is first air-cooled to 280°C at a cooling rate of 24°C / s, and then water-cooled to room temperature at a cooling rate of 40°C / s to complete the preparation of thick-gauge GPa grade hot-dip galvanized duplex steel.
[0067] The thickness of this GPa grade duplex steel is 3.2 mm, and its chemical composition by weight percentage is: C 0.10%, Mn 2.10%, Si 0.55%, P 0.022%, Cr 0.45%, Nb 0.030%, Mo 0.14%, Als 0.035%, with the balance being Fe and unavoidable impurities; the volume fraction of martensite in the matrix is 42%.
Claims
1. A method for controlling the oxide layer at the reactive interface of thick-gauge GPa-grade hot-dip galvanized duplex steel, characterized in that, Includes the following steps: 1) Hot rolling: A multi-stage hot rolling cooling process is adopted; The hot rolling process involves heating at 1200–1250°C, followed by rough rolling and then finish rolling. The initial rough rolling temperature is 1080–1130°C, and the final finish rolling temperature is 820–850°C. The coiling is achieved through two stages of water cooling. The first stage involves water cooling to 600–630°C, followed by air cooling to 540–560°C, and the second stage involves water cooling to 180–220°C before coiling. 2) Pickling: belt speed is 85-95 m / min, acid temperature is 85-88℃; 3) Pretreatment: The strip steel is surface cleaned and dried at a temperature of 130-150℃ for 4-5 minutes. 4) Annealing and Reduction: The strip steel is fed into a continuous annealing furnace at a speed of 50–52 m / min. A gradient heating process is adopted, first heating to 820–845℃ at 18–22℃ / s, then heating to 850–865℃ at 5–8℃ / s, and holding for 2–3 seconds; subsequently cooling to 680–690℃ at 8–10℃ / s, and holding for 3–5 seconds; 15%–18% H2 and 81%–85% N2 by volume are introduced into the furnace, and the reduction dew point is controlled at -45℃ to -50℃; then it enters the pre-oxidation stage, using a nitrogen-oxygen mixed gas with a flow rate of 12–15 m³ / s. 3 / h, the humidification dew point is set to -8℃~-10℃, and the grate dew point is set to -15℃~-20℃; 5) Hot-dip galvanizing: The annealed strip steel is immersed in molten zinc at a temperature of 455-465℃ for 4-6 seconds. The chemical composition of the zinc liquid, by weight percentage, includes: Zn≥99.5%, Al 0.22%~0.26%, Pb≤0.002%, and also contains 30~50ppm of rare earth element Ce, with the balance being unavoidable impurities; 6) Post-treatment: Use air knife to purge, with an air knife pressure of 0.11-0.15 MPa and a distance of 15-25 mm between the air knife and the strip to remove excess zinc liquid from the surface of the strip; then air cool to 200-300℃ at a cooling rate of 15-30℃ / s, and then water cool to room temperature at a cooling rate of 30-50℃ / s. The chemical composition of the aforementioned thick-gauge GPa grade hot-dip galvanized duplex steel, by weight percentage, includes: C: 0.07%~0.12%, Mn: 2.0%~2.3%, Si: 0.4%~0.6%, P≤0.025%, Cr: 0.30%~0.5%, Nb: 0.015%~0.035%, Mo: 0.10%~0.20%, Als: 0.020%~0.05%, balance Fe.
2. The method for controlling the oxide layer at the reaction interface of thick-gauge GPa-grade hot-dip galvanized duplex steel according to claim 1, characterized in that, The thickness of the thick-gauge GPa grade hot-dip galvanized duplex steel plate is 2.5 to 3.5 mm.
3. The method for controlling the oxide layer at the reaction interface of thick-gauge GPa-grade hot-dip galvanized duplex steel according to claim 1, characterized in that, The microstructure of the thick-gauge GPa grade hot-dip galvanized duplex steel is a ferrite-martensite dual-phase structure, with a martensite volume fraction of 30% to 45%.
4. The method for controlling the oxide layer at the reaction interface of thick-gauge GPa-grade hot-dip galvanized duplex steel according to claim 1, characterized in that, The nitrogen-oxygen mixture contains, by volume percentage: 20%–25% oxygen, with the remainder being nitrogen and unavoidable impurity gases.
Citation Information
Patent Citations
Thick hot galvanized complex phase steel and production method thereof
CN110358967A
Process for strengthening binding force of GPa-grade hot-dip galvanized dual-phase steel coating
CN122214762A